Characterization of tar-like material and producible oil in Misoa C2 and C3 reservoir sands of the Area 2 South (Ceuta Field, Venezuela). (April 2017) - Márquez, G.; Escobar, M.; Esquinas, N.; Duno, L.; Martín-Martín, J.D.; Permanyer, A.
Abstract: Here we characterized asphaltic oil occurrences in the Misoa C2 and C3 reservoirs within Area 2 South of the Ceuta Field (Lake Maracaibo Basin, NW Venezuela). To perform the geochemical and petrological characterization of the C2 and C3 sub-units, which cover an interval in which tar-like material was detected, we analyzed core (18) and cutting (123) samples using the Rock-Eval 6 technique in reservoir mode. Samples were studied under fluorescence light and scanning electron microscopy (SEM), showing the presence of two charges of oils and the relationships within silica cements and clay minerals. To evaluate vertical inter-reservoir communication and lateral intra-reservoir continuity, we also studied 12 oil samples from wells in Area 2 South. Biomarkers and isotopic signatures were examined using gas chromatography-mass spectrometry (GC-MS) and isotope ratio mass spectrometry (IRMS). The results suggest that oil and core extracts belongs to a single family derived from two pulses of hydrocarbon generation from the La Luna source rock, which was deposited in a marine reducing environment. The oil samples are a mixture of a paleobiodegraded oil charge and a later fresh, more mature oil recharge. The geochemical analyses also evidence that the formation of heavy oil tar zones can be related to biodegradation and in-reservoir oil mixing, though other formation mechanisms for the tar are also feasible. Finally, the GC fingerprints of the oils are indicative of lateral reservoir continuities across the F-1 and F-2 faults and vertical communication between the Misoa C2 and C3 sub-units in Area 2 South, suggesting that tar occurrences do not act as permeability barriers within the two reservoirs studied. Highlights: This work is an analysis of 12 oils and 141 reservoir rock samples from Area 2 South. Results from petrographic analyses allowed distinguish two types of bitumen. Rock-Eval pyrolysis denoted the presence of tar patches in the Misoa C2 and C3 bodies. Oil samples fall into one family derived from two pulses from the La Luna source rock. GC fingerprints showed lateral and vertical connectivity of the C2 and C3 reservoirs.